Pendampingan Pembuatan Digital Assessment dengan Quizizz sebagai Media Evaluasi Guru TK/RA - Yana Cahyana; NinaNina Puspitaloka (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
The integration of technology into education, particularly in the area of learning assessment, has been recognized as an essential component in supporting effective, efficient, and interactive learning processes. Nevertheless, sufficient competencies in designing digital assessments had not yet been possessed by all teachers. Accordingly, this community service program was conducted to strengthen the competencies of teachers at TK/RA At-Taqwa in designing digital assessments through the use of the Quizizz application as an alternative learning evaluation tool. The program was implemented through three sequential stages, namely preparation, implementation, and evaluation. During the implementation stage, instructional materials were delivered, followed by hands-on practice sessions and intensive mentoring provided to all participants. The findings demonstrated that the participating teachers were able to understand the development process and independently create interactive quizzes using Quizizz. In addition, highly positive responses were reported by the participants, and no significant technical constraints were encountered throughout the implementation. Consequently, the program was shown to have contributed to enhancing teachers’ competencies in utilizing technology to conduct more interactive, innovative, and effective learning assessments.